Peran Guru Bimbingan dan Konseling Dalam Mengatasi Tindak Indisipliner Peserta Didik di Sekolah SMA Negeri 4 Metro - Ghulam Murtadlo; Janah Evasari; Putri Purriama Sari (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This study aims to determine the role of guidance and counseling teachers at SMA Negeri 4 Metro in overcoming disciplinary actions, in overcoming smoking habits in students. Data collection methods in this study used interviews, observation, and documentation. The data sources in this study are guidance and counseling teachers and deputy curriculum of SMA Negeri 4 Metro. The results of this study explain that the smoking habit carried out by students is slowly reduced due to intensive habituation by counseling guidance teachers through learning activities in class and also outside the classroom in the form of individual guidance, as well as involving parents in overcoming this problem.This study aims to determine the role of guidance and counseling teachers at SMA Negeri 4 Metro in overcoming disciplinary actions, in overcoming smoking habits in students. The data collection method in this study used interviews, observation, and documentation. The data sources in this study are guidance and counseling teachers and deputy curriculum of SMA Negeri 4 Metro.The results of this study explain that the smoking habit carried out by students is slowly reduced due to intensive habituation by counseling guidance teachers through learning activities in class and also outside the classroom in the form of individual guidance, as well as involving parents in overcoming this problem.Â